1993
DOI: 10.3758/bf03197194
|View full text |Cite
|
Sign up to set email alerts
|

Context effects in repetition priming are sense effects

Abstract: This article reports three experiments that investigate the role of context in repetition priming using a lexical decision task. The experiments show that repetition priming is either eliminated or significantly reduced if a change in context also alters the perceived sense of a nonhomographic target word. If perceived sense is not altered, a change in context is inconsequential. This points to the important role played by perceived sense in repetition priming. An explanation within a sense-specific activation… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

7
28
2

Year Published

1995
1995
2018
2018

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 32 publications
(37 citation statements)
references
References 40 publications
7
28
2
Order By: Relevance
“…In addition, Ratcliff (1979, 1986) and Goshen-Gottstein and Moscovitch (1995) investigated facilitations in making lexical decisions for words that have been viewed previously in the context of prime words. Greater priming is found when words are presented in the same context than in a different context, as before (but see also Bainbridge, Lewandowsky, & Kirsner, 1993;Carroll & Kirsner, 1982;Dagenbach, Horst, & Carr, 1990;Neely & Durgunoglu, 1985;Durgunoglu & Neely, 1987;Smith, MacLeod, Bain, & Hoppe, 1989). Depending on the particular strategies and information storage that result when different methodologies are used, new-associations priming may rely on storage of information in various subsystems.…”
Section: Discussionmentioning
confidence: 54%
“…In addition, Ratcliff (1979, 1986) and Goshen-Gottstein and Moscovitch (1995) investigated facilitations in making lexical decisions for words that have been viewed previously in the context of prime words. Greater priming is found when words are presented in the same context than in a different context, as before (but see also Bainbridge, Lewandowsky, & Kirsner, 1993;Carroll & Kirsner, 1982;Dagenbach, Horst, & Carr, 1990;Neely & Durgunoglu, 1985;Durgunoglu & Neely, 1987;Smith, MacLeod, Bain, & Hoppe, 1989). Depending on the particular strategies and information storage that result when different methodologies are used, new-associations priming may rely on storage of information in various subsystems.…”
Section: Discussionmentioning
confidence: 54%
“…As predicted by the episodic view, targets read in isolation showed more priming than did targets read in sentences. Alternatively, Bainbridge et al (1993) suggested that this pattern of results is due to the greater tendency for the same sense of a word to be activated if it is presented singly both at study and at test; embedding the target in a context at study may reduce priming if the sense biased by the context differs from that activated when the target is tested alone.…”
Section: Episodic Contextmentioning
confidence: 99%
“…Additional support for the sense-specific account was obtained by Bainbridge, Lewandowsky, and Kirsner (1993). In their first experiment, subjects were asked to make lexical decisions about nonhomographic items presented as possible sentence completions.…”
Section: Episodic Contextmentioning
confidence: 99%
See 1 more Smart Citation
“…Chicago, 1994 The conceptual meaning hypothesis was developed to address contextual manipulations such as those created by relatedness priming in lexical decision, in which a change in a prime's meaning results in little or no facilitation (Bainbridge, Lewandowsky, & Kirsner, 1993;Lewandowsky, Kirsner, & Bainbridge, 1989;Masson & Freedman, 1990). In other words, facilitation due to repetition will be reduced if the conceptual meaning is not instantiated on each occurrence.…”
mentioning
confidence: 99%